Effect of the Atlantic Multidecadal Variability on the Global Monsoon. Issue 3 (8th February 2019) - Monerie, Paul‐Arthur; Robson, Jon; Dong, Buwen; Hodson, Dan L. R.; Klingaman, Nicholas P.
Abstract: We assess the effect of the Atlantic multidecadal variability (AMV) on the global monsoon using idealized simulations. Warm AMV phases are associated with a significant strengthening of monsoon precipitation over Northern Africa and India, and anomalously weak monsoon precipitation over South America. Changes in monsoon precipitation are mediated by a change in atmospheric dynamics, primarily associated with a shift in the circulation related to both an enhanced interhemispheric thermal contrast and the remote impact of AMV on the Pacific Ocean, through changes in the Walker circulation. In contrast, the thermodynamic changes are less important. Further experiments show that the impact of AMV is largely due to the tropical component of the sea surface temperature anomalies. However, the extratropical Atlantic also plays a role, especially for northern Africa. Finally, we show that the effect of AMV on monsoons is not linearly related to the magnitude of warming. Plain Language Summary: Global monsoon precipitation variability has substantial effects on about two thirds of the world's population. Therefore, understanding the factors that drive tropical precipitation is societally important. Here we focus on the effect of North Atlantic sea surface temperature (NASST) variability on global monsoon. To do so we use a set of climate model experiments, in which we add a surface temperature anomaly over the North Atlantic Ocean. The novelty of the analysis relies on the decomposition of precipitation changes to understand better their origins. We find that NASST changes have strong impacts on Sahel and Indian summer precipitation and monsoon domain sizes, through shifting northward the atmospheric patterns of moisture convergence. Changes involve increases in the large‐scale warming of the Northern Hemisphere and forcing of the eastern equatorial Pacific Ocean temperature. We highlight the tropical Atlantic basin as critical to explain the effects of NASST variability over the global monsoon. We found that changes in monsoon precipitation are sensitive to the magnitude of the NASST warming. Key Points: Changes in atmospheric circulation dominate the AMV effect on monsoons, while thermodynamic changes are moderate The tropical North Atlantic largely forces AMV effects, by strengthening interhemispheric thermal gradients and the Walker circulation The effects of AMV are not linearly related to the magnitude of warming